2014
DOI: 10.1097/hco.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracorporeal membrane oxygenation circulatory support in the ‘crash and burn’ patient

Abstract: In this review, based on the daily routine of the Hershey group using ECMO for therapy of advanced cardiogenic shock, the application of ECMO is described. The aim is to share our hands-on experience during emergent implantation and to contribute to the knowledge within the field of mechanical circulatory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 11 publications
4
89
0
Order By: Relevance
“…Available data from other centers show that usually 10–60% of patients on VA‐ECMO develop severe LV distension, with the highest rates observed in neonates and children . Similar to other centers with low rates of severe LV distension , we also pursue aggressive prophylaxis of LV distension . Our approach includes close monitoring of PCWP and frequent cardiac ultrasound exams, diuretic therapy, or renal replacement therapy to correct fluid overload, and titration of inotropes to utilize residual left ventricular function.…”
Section: Discussionmentioning
confidence: 94%
“…Available data from other centers show that usually 10–60% of patients on VA‐ECMO develop severe LV distension, with the highest rates observed in neonates and children . Similar to other centers with low rates of severe LV distension , we also pursue aggressive prophylaxis of LV distension . Our approach includes close monitoring of PCWP and frequent cardiac ultrasound exams, diuretic therapy, or renal replacement therapy to correct fluid overload, and titration of inotropes to utilize residual left ventricular function.…”
Section: Discussionmentioning
confidence: 94%
“…It is technically simple to implement requires no arterial cannulation and no pump. This may prove particularly useful in centers that do not have rapid access to advanced techniques such as ECMO ().…”
Section: Discussionmentioning
confidence: 99%
“…There are no guidelines regarding sufficient cardiac recovery for primary weaning. El‐Banayosy and coworkers proposed a left ventricular ejection fraction of more than 30% and normal filling pressures of less than 18 mm Hg during pump stop as sufficient weaning criteria . However Loforte et al showed in their retrospective analysis that patients being weaned from ECLS with a left ventricular ejection fraction of less than 40% at weaning showed a 12‐month survival of less than 50% .…”
Section: Discussionmentioning
confidence: 99%
“…During the ECLS weaning, the cardiac function was evaluated by echocardiography and invasive hemodynamic measurements with a pulmonary artery catheter. An insufficient cardiac recovery was considered if left ventricular function was less than 30% and pulmonary wedge pressure and/or central venous pressure was higher than 18 mm Hg during pump stop phases .…”
Section: Methodsmentioning
confidence: 99%